Fikih Jihad Hizbut Tahrir Indonesia - Azman, Azman (Al-Daulah : Journal of Criminal Law and State Administration Law, 2015)
For Hizb ut-Tahrir Indonesia kifayah legal jihad is a religious obligation. Jihad is the attack against an enemy that does not implement Islamic Shari'a. So when the enemy attacked  then becomes fard ayn (on every Muslim). Jihad is an absolute obligation, not limited by nothing and no disaratkan with nothing, jihad is an offensive war to elevate the word of Allah. Offensive war must be done to spread Islam and spreading propaganda even though the unbelievers are not attacking Muslims.